A Companion to Isidore of Seville
1 online resource
Keywords: A Companion to Isidore of Seville presents nineteen chapters from leading international scholars on Isidore of Seville (d. 636), the most prominent bishop of the Visigothic kingdom in Hispania in the seventh century and one of the most prolific authors of early medieval western Europe. Introductory studies establish the political, religious and familial contexts in which Isidore operated, his key works are then analysed in detail, as are some of the main themes that run throughout his corpus. Isidore's influence extended across the entire Middle Ages and into the early modern period in fields such as church governance and pastoral care, theology, grammar, science, history-writing, linguistics, all topics that are explored in the volume. Graham Barrett, Winston Black, José Carracedo Fraga, Santiago Castellanos, Pedro Castillo Maldonado, Jacques Elfassi, A. T. Fear, Amy Fuller, Raúl González Salinero, Jeremy Lawrance, Céline Martin, Thomas O'Loughlin, Martin J. Ryan, Sinéad O'Sullivan, Mark Lewis Tizzoni, Purificación Ubric Rabaneda, Faith Wallis, Immo Warntjes, and Jamie Wood.